Distribution of financial resources by areas of investments in the human capital of the region - Lev S. Mazelis (Limited liability company “Scientific and Educational Initiative”, 2021)
Introduction. The study has been conducted within the framework of the urgent scientific and practical task of accumulation and development of human capital of Russian regions. Under the conditions of risks and limited resources, the regional management faces the task of optimal distribution of financial resources invested in the development of human capital and improvement of the quality of life. The study aims to build and test the dynamic optimization model of financial resources distribution by areas of investment in human capital through the example of the Primorye Territory (Russian Federation).